Patient specific instrumentation in total knee arthroplasty - Colombelli, Andrea; Belluati, Alberto; Rizqallah, Yousef; Guerra, Giovanni; Busatto, Carlo (Acta Biomedica Atenei Parmensis, 2017)
Background and aim of the work: The international literature and analysis of the prosthetic registers highlight a significant relationship between the alignment of the components and the survival of prosthetic implants of the knee. The patient specific instrumentation (PSI) technology exploits the data obtained with the MRN for the production of cutting blocks (CB) useful to a TKA. Revisiting the recent international literature, comparing the results of the conventional method and PSI, numerous studies confirm a statistically significant difference of inliers (± 3 degrees) for HKA. The purpose of this retrospective study was to investigate whether these statistically significant difference is also present in our group. Methods: Postoperative radiographic measures of alignment based on a mechanical limb axis (hip-knee-ankle angle, HKA) of 180° were sought. A range of 180° ± 3° varus/valgus was defined as optimal for mechanical axis. Results: The percentage of knees that had a HKA within ±3° of the desired value was 92.2. Conclusion: the CB did accurately produce the desired HKA. The PS system is an effective and reproducible, whose organizational effort is fully justified.